Why are there so many banking crises? : the politics and policy of bank regulation - Rochet, Jean-Charles. (Princeton, NJ : Princeton University Press, 2008)
This book is all about why there are so many banking crises.
Includes bibliographical references.
aia 3/05/13
Loan
Keywords: Bank failures; Banks and banking; Lenders of last resort